Isolation and Identification of Bacillus cereus s.l. From Ready-to-eat Cereals - Loo, Chia Hui (Universiti Malaysia Sarawak (UNIMAS), 2010)
Bacillus cereus is a soil inhabitant gram positive bacterium, but can also be found in raw or cooked starchy foods, such as the highly-processed ready-to-eat (RTE) foods. In this study, Bacillus cereus s.l. was isolated from RTE cereals and identified using biochemical tests. A total of 30 RTE cereals were purchased from the local supermarket in Kuching and Kota Samarahan, Sarawak from December 2009 until February 2010. Samples were enriched in Tryptic Soy Broth for 24 hours. Then, Bacillus cereus selective agar (base) was used to isolate the colonies. Isolated presumptive colonies were based on their morphological growth on the agar, which are large, round and pinkish white colonies. After that, Gram stain and a series of biochemical tests such as catalase test, motility, Tryosine Decompose, Glucose fermentation, VP test and Indole test were carried out. Later, the most highly suspected colonies were subjected to BBL Crystal™ Identification Systems Gram - Positive ID Kit test for further confirmation of the organisms. Result has revealed that four food samples were detected to be contaminated by Bacillus cereus s.l..Therefore, it is very crucial for food industries and health department to pay attention to the safety on consumption of RTE cereals, as it is possible that Bacillus cereus s.l. exist in high count number and pose hazardous effects to consumers.